Dupilumab in the Management of Moderate-to-Severe Atopic Dermatitis: an Evidence-Based Review of Efficacy, Quality of Life Impact, and Safety Profile - Smereka, Szymon; Jabłoński, Wiktor; Raszewska, Julia; Osyra, Paulina; Wolińska, Natalia; Frycz, Jan (Dermatology Review/Przegląd Dermatologiczny, 2025)
Atopic dermatitis is a chronic, inflammatory skin disease that significantly impacts patients’ quality of life. Its persistent symptoms such as pruritus, skin barrier dysfunction, and associated comorbidities can be debilitating. Conventional treatments for atopic dermatitis, including systemic corticosteroids and immunosuppressants, are often associated with a high risk of adverse effects, particularly with long-term use, which limits their application due to patient safety concerns. In contrast, dupilumab, a monoclonal antibody that blocks interleukin-4 and interleukin-13 by targeting the IL-4 receptor alpha, has emerged as a promising therapeutic option, as it effectively disrupts the key pathophysiological pathways driving atopic dermatitis. This paper presents a review of the efficacy, safety, and impact on quality of life associated with treatment using dupilumab. The information is derived from data obtained through clinical trials, open-label extension studies, and real-world assessments. The data from the aforementioned studies demonstrate significant improvements in disease progression, including symptom relief and, importantly, enhanced quality of life as reported by patients. Additionally, dupilumab exhibits a favorable safety profile, characterized by low rates of serious adverse events; however, occurrences of conjunctivitis and injection site reactions have also been documented. This review offers a comprehensive analysis of dupilumab’s role in the treatment of atopic dermatitis, highlighting its suitability for long-term use as well as its efficacy in patients who exhibit an inadequate response to conventional therapies.